Sustainability Impact of COVID-19: Insights for the Event Tourism Management Industry - Rakesh, Sarpal; Krishan, Kandiah (INTI International University, 2021)
This literature review looks at the macro environmental impacts of COVID-19 on the event tourism industry from three aspects, namely, environmental, economic, and technological factors. The literature is then looked at from a sustainability perspective which questions what has happened to the event tourism experience, whether the pandemic has permanently changed the event landscape, and if life would return to how it used to be before the outbreak of the virus. Paired with theoretical discussion, the findings include positive and negative environmental impacts, the acceptance of sustainable event organizing that prioritizes natural capital, economic drawbacks and solutions, and the technological adaptations to event tourism. The relevant theories such as the macro-environmental factors and Theory of Planned Behavior had been reflected in this review. The significance of this review will help develop further arguments on issues that are indirectly affected by the changes of today.